Analisis Perbandingan Metode Tradisional Dengan Metode Activity Based Costing Dalam Menentukan Harga Pokok Produksi - Muhammad Joni Barus; Chairunisa Wiguna; Shofwan Andri (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2023)
The research conducted by the author aims to find out and analyze the determination of the cost of production based on the Activity Based Costing (ABC) method at Akbar Jaya Bakery and to find out whether the management at Akbar Jaya Bakery can carry out a more accurate analysis of the volume of sales required for decision making using the method Activity Based Costing (ABC). The results showed that the calculation of the Cost of Production Using the Activity Based Costing Method was more accurate and profitable compared to the traditional method, because the Activity Based Costing Method yielded smaller results compared to the Traditional Method so that the company could reconsider the method used in determining its Cost of Production.